(3VQGFQ GdTYQs - (3eMeO Hf LYaQ GdJejej , GdbRGR , CHh YHO Gddg,J (B412 (3g` s ((3YHOGdQMef Hf YHOGddg GdeYGaQi GdeWQR s)
(3ChdgG (B:s
(3gPG cJGH CPcQ ajg EfTGA Gddg eG jLhR ddTGYQ YfO GdVQhQI ef GdRjGOI hGdfbUGf hGdEJSGY ai SGFQ GdeYGfi ef GdJbOje hGdJCNjQ hGdbdH hGdEHOGd CdN s
(3efbhdI Yf fSNI cJHJ SfI (B439s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B71 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B148s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B498 s
Keywords: (3GdCOHs